1983
DOI: 10.1080/02786828308958651
|View full text |Cite
|
Sign up to set email alerts
|

Response Characteristics of the Particle Measuring Systems Active Scattering Aerosol Spectrometer Probe (ASASP–X)

Abstract: Response characteristics of the Particle Measuring Systems active scattering aerosol spectrometer probe are investigated. Response measurements on monodisperse nonabsorbing latex and highly absorbing nigrosin aerosols are in general agreement with theoretical predictions, although the predicted fine-structure resonances for micron-size particles are not experimentally resolved. The results suggest the manufacturer's instrument calibration (or a slight modification thereof) is appropriate for spherical particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
1
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(79 citation statements)
references
References 3 publications
8
69
1
1
Order By: Relevance
“…Prior studies have reported the refractive index for nigrosin aerosol in the visible spectral region (Garvey and Pinnick, 1983;Lack et al, 2006;Flores et al, 2009;Lang-Yona et al, 2009;Bluvshtein et al, 2012). The reported values are generally consistent: 1.67 + 0.26i at 633 nm (Garvey and Pinnick, 1983); 1.70 (±0.04) + 0.31 (±0.05)i at 532 nm (Lack et al, 2006); 1.649 (±0.007) + 0.238 (±0.008)i at 532 nm (Dinar et al, 2008) …”
Section: Comparison Of Nigrosin Refractive Index To Published Values supporting
confidence: 64%
“…Prior studies have reported the refractive index for nigrosin aerosol in the visible spectral region (Garvey and Pinnick, 1983;Lack et al, 2006;Flores et al, 2009;Lang-Yona et al, 2009;Bluvshtein et al, 2012). The reported values are generally consistent: 1.67 + 0.26i at 633 nm (Garvey and Pinnick, 1983); 1.70 (±0.04) + 0.31 (±0.05)i at 532 nm (Lack et al, 2006); 1.649 (±0.007) + 0.238 (±0.008)i at 532 nm (Dinar et al, 2008) …”
Section: Comparison Of Nigrosin Refractive Index To Published Values supporting
confidence: 64%
“…In a previous aerosol study (Garvey and Pinnick 1983), the refractive index of pure nigrosin was taken to be 1.67-0.26i . Water solutions of pure nigrosin, pure ammonium sulfate, and various mixtures of the two were nebulized using bubblers, as shown in Figure 5.…”
Section: T C Bond Et Almentioning
confidence: 99%
“…In this case, the mobility diameter and mass equivalent diameter are identical, because nigrosin particles are spherical. C * abs (λ) was calculated using Mie theory for n = 1.70 -0.30i (Lack et al 2006) and n = 1.67 -0.26i (Garvey and Pinnick 1983) at λ = 565 nm and is shown in Figure 11 for comparison. C abs (λ) was much larger than C * abs (λ), especially at D nigrosin smaller than 300 nm.…”
Section: Size Dependence Of C Abs () For Nigrosinmentioning
confidence: 99%